2014
DOI: 10.1007/s12072-014-9574-0
|View full text |Cite
|
Sign up to set email alerts
|

Favorable adverse event profile of sofosbuvir/ribavirin compared to boceprevir/interferon/ribavirin for treatment of hepatitis C

Abstract: SOF/RBV treatment was associated with fewer side effects than BOC-based triple therapy, appearing to be a safer and more tolerable alternative for HCV GT-1 subjects. These results show that emerging IFN-free therapies may enhance patient adherence, allowing treatment of larger number of patients with improved efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
3
2
Order By: Relevance
“…[25] In addition, hematologic abnormalities were more prominent among the triple-therapy group in other studies, for example, Satsangi et al, [32] and Wei et al [33] Adding IFN to other DAAs was associated with anemia and leucopenia in other studies. [37,38] In contrast to our study, Ahmed et al found no significant effect of adding IFN to a SOF--RBV regimen on hemoglobin and leucocyte levels. [31] In our triple-therapy group, the drop of HCV RNA was greater: mean values of HCV RNA were lower among the triple-therapy group within 4 weeks of treatment, that is, (354.16 ± 1444.84 IU/mL, 27.5 ± 122.98 IU/mL) for double and triple therapy respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…[25] In addition, hematologic abnormalities were more prominent among the triple-therapy group in other studies, for example, Satsangi et al, [32] and Wei et al [33] Adding IFN to other DAAs was associated with anemia and leucopenia in other studies. [37,38] In contrast to our study, Ahmed et al found no significant effect of adding IFN to a SOF--RBV regimen on hemoglobin and leucocyte levels. [31] In our triple-therapy group, the drop of HCV RNA was greater: mean values of HCV RNA were lower among the triple-therapy group within 4 weeks of treatment, that is, (354.16 ± 1444.84 IU/mL, 27.5 ± 122.98 IU/mL) for double and triple therapy respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…This strongly suggests that ITPA deficiency is still predictive of anaemia even when RBV is combined with DAAs with a poor haematological tolerance as recently reported in an HCV-monoinfected population treated with TLV [28]. Moreover, even though RBV is combined with a second-generation DAA like sofosbuvir with a better haematological tolerance profile, anaemia can still occur in 25% of patients [29]. As the choice of RBV dose is not currently validated in these new therapies with DAAs, ITPA genotyping may be still of interest to detect patients early with a higher risk of developing severe anaemia and would be useful to recommend either RBV dose adjustment or a specific follow-up during therapy.…”
Section: Discussionsupporting
confidence: 53%
“…Neutropenia still occurs with any PegIFN containing regimen regardless of the DAA included [42][43][44][45]. IFN-free regimens do not cause neutropenia suggesting that PegIFN is the cause rather than CHC, DAA or RBV [43].…”
Section: Discussionmentioning
confidence: 97%